Change of Calcium Concentrations in Forest Soils by Plant Species and Soil Depth - Erdem, Ramazan (Kastamonu University, 2022)
One of the most important factors playing role in plant development is the nutrient element content of the soil. Being one of the fundamentally necessary macronutrients for plant nourishment, calcium (Ca) plays an important role in the growth and development of a plant. Thus, even though many studies have been carried out on the change of Ca concentration in agricultural soils, the number of studies examining this subject for forest soils is very limited. In the present study, it was aimed to compare the concentrations of Ca in soil and plant organs for the soils, where different forest trees are grown. Within this scope, leaf, bark, wood, cone, and root samples were collected from Turkish fir, black pine, Scotch pine, and Oriental beech species and soil samples were taken from the surface, mid-deep, and deep soil levels. Then, the Ca concentrations were compared. As a result, it was determined that Ca concentrations statistically significantly vary between leaves, roots, and woods of plants and between mid-deep and deep soils by species (p
Keywords: Engineering; Mühendislik; Soil; Forest; Nutrient Element; Ca; 2. Zero hunger; 15. Life on land